2011
DOI: 10.1111/j.1471-4159.2011.07446.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking epidermal growth factor receptor attenuates reactive astrogliosis through inhibiting cell cycle progression and protects against ischemic brain injury in rats

Abstract: J. Neurochem. (2011) 119, 644–653. Abstract Excessive astrogliosis is a major impediment to axonal regeneration in CNS disorders. Overcoming this inhibitory barrier of reactive astrocytes might be crucial for CNS repair. Up‐regulation and activation of epidermal growth factor receptor (EGFR) has been shown to trigger quiescent astrocytes into reactive astrocytes in response to several neural injuries. In this study, we investigated the effects of EGFR blockade in cultured astrocytes exposure to oxygen–glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…It has been reported that several signaling molecules, including bFGF, EGF, endothelin‐1, sonic hedgehog, and galectin‐1/3, are involved in proliferation of astrocytes in response to brain injury (Gadea et al, ; Kang et al, ; Pitter et al, ; Sirko et al, ; Sirko et al, ; Yang et al, ). However, these molecules also appear to affect other reactive responses such as induction of GFAP , and thus it remains to be elucidated how these molecules affect cell proliferation of reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several signaling molecules, including bFGF, EGF, endothelin‐1, sonic hedgehog, and galectin‐1/3, are involved in proliferation of astrocytes in response to brain injury (Gadea et al, ; Kang et al, ; Pitter et al, ; Sirko et al, ; Sirko et al, ; Yang et al, ). However, these molecules also appear to affect other reactive responses such as induction of GFAP , and thus it remains to be elucidated how these molecules affect cell proliferation of reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Primary astrocytes were obtained and purified as previously described (41) with minor modifications. Briefly, cerebral cortices from 1-day-old Sprague-Dawley rat pups were extracted and dissociated by mechanical trituration and 0.125% Trypsin-EDTA (Invitrogen) treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of other membrane receptors, such as angiotensin II receptors and adrenergic receptors, were also reported to transactivate EGFR signaling pathway (Chen et al, 2012;Fischer et al, 2006;Flannery and Spurney, 2006). In addition, EGFR is also known to play a role other than the usual ligand-dependent one, especially after the onset of CNS disorders (Planas et al, 1998;Qu et al, 2012;Wong and Guillaud, 2004;Yang et al, 2011). Our recent published study showed that EGFR exerted an important effect on regulating microglia activation, however, blockade of EGFR phosphorylation could effectively inhibit the hypertrophy of LPS-exposed microglia, and attenuate the production of inflammatory mediators induced by either LPS stimulation in vitro or experimental spinal cord trauma (Qu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%